Governing urban wetlands for green growth in the Western Region Megapolis of Sri Lanka - Flower, Ben; Amerasinghe, Priyanie H.; Miranda, Ramona (International Water Management Institute, 2019)
The Western Region Megapolis (WRM) of Sri Lanka, the conurbation associated with Greater Colombo and covering the entire Western Province, is the thriving economic center of the country. According to the State of Sri Lankan Cities 2018 report (GoSL 2018), the city accounts for 40% of Sri Lanka’s gross domestic product (GDP), 30% of its population and is the nation’s administrative center. The WRM is also endowed with wetlands of international importance. This includes the Bellanwila-Attidiya marshes: a 370-ha freshwater marsh in southern Colombo rich in biodiversity (Box 1); the Colombo Flood Detention Area: a 400-ha network of marshes and canals that traverse the DISCUSSION BRIEF An aerial view of the city of Colombo in Sri Lanka with its network of wetlands supporting urban dwellers - A hub for green growth. Photo: Martin Seemungal city; and the Muthurajawela marsh: a 2,500-ha saltwater marsh in northern Colombo, which is the largest saline peat bog in Sri Lanka (IUCN and CEA 2006). The aim of this brief is to support the efforts of the Government of Sri Lanka to leverage the WRM wetlands to foster green growth. Green growth promotes economic development alongside environmental sustainability, and is gaining traction as a model to achieve sustainable urban development globally (Hammer et al. 2011). According to OECD (2013: 9), governments promote green growth “to create jobs and attract firms and investment, while improving local environmental quality and addressing global environmental challenges, particularly climate change.”